Therapeutic potential of Nitazoxanide against Newcastle disease virus: A possible modulation of host cytokines. (July 2020) - Antony, Ferrin; Vashi, Yoya; Morla, Sudhir; Vandna,; Mohan, Hari; Kumar, Sachin
Abstract: Newcastle disease (ND) is prevalent among the domesticated and the wild birds and is caused by the avian paramyxovirus serotype-I (APMV-I). It is commonly known to affect chicken, pheasant, ostrich, pigeon and waterfowl. Depending on the virulence, the velogenic NDV strains cause severe respiratory and nervous disorders with a high mortality rate. The live and killed vaccines are available for the prevention of infection in the market, but the drug for the treatment is not available. Nitazoxanide (NTZ), a member of thiazolides, is an antiparasitic drug . In the present study, the effect of NTZ on the NDV replication was explored. The experiments were conducted in chicken fibroblast cells (DF-1), PBMC, embryonated chicken eggs, and two-week old chickens. The inhibition of the NDV was observed upon post-treatment of NTZ at a concentration of ~12.5 μM. Cytokine profiling of the DF-1, PBMC, and chicken embryonic tissue treated with NTZ revealed significant upregulation in all the cytokines studied except for IL-1β in DF-1 cells. It is plausible that NTZ is involved in causing immune-modulatory effects in poultry. NTZ treatment in two weeks old chicken showed significant reduction in NDV replication in trachea, and lungs, respectively, at 72 h post-infection. Encouraging results from the present study warrants repurposing NTZ as a drug for the treatment of viral infection in poultry. It will also pave the way towards understanding of similar effect against other animal pathogens.